تقييم كفاءة الخدمات التعليمية في مدينة بلدروز - صائل محمد الجبوري, منذر; ثامر سعيد النداوي, ماهر (Al-Adab Journal, 2018)
Most Iraqi cities face a number of problems and challenges, of poor public services distribution in general education services in particular, and also pinned down in residential neighborhoods and not taking into account local planning standards set by the Iraqi Ministry of Planning in the distribution to cope with the population growth, urbanization, and population needs these services, research included studying the reality of educational services in the city of Baladruz, 2015 came and through a number of indicators of efficiency and application to see the statement of the degree of efficiency and suitability criteria of local planning that meets the needs of the residents of Baladruz town Done conduct spatial analysis and evaluation fact, the spatial distribution of educational services by comparison standards of planning for the Ministry of planning and the Iraqi educational Services, and has a clear decrease in the size and distribution services provided showing the population of the city, and this shortage is not only the result of a lack of presence, but also the result of the vision planning deficit and the absence of future plans that take into account the increasing size of the population of the city, and at the end Find found a number of conclusions and recommendations that the researchers hope to achieve something of interest in the development of cities and our beloved country.